2022
DOI: 10.1186/s12884-022-04521-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased blastomere number is associated with higher live birth rate in day 3 embryo transfer

Abstract: Purpose To study the relationship between blastomere number and pregnancy outcomes of day 3 embryo transfers. Methods This retrospective cohort study included 2237 fresh single day 3 embryo transfer cycles from October 2013 to November 2020. Patients were divided into six groups according to the blastomere number on day 3: ≤ 6-cell (n = 100), 7-cell (n = 207), 8-cell (n = 1522), 9-cell (n = 187), 10-cell (n = 91) and ≥ 11-cell (n = 130). Generalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Their results showed that for embryos with normal cleavage patterns, developmental potential, implantation, and LBRs increased with cell number. Moreover, Tian et al [15] found that the LBRs were signi cantly higher in patients transplanted with 10-cell embryos (OR 1.62, 95% CI 1.03-2.53; P = 0.035) and ≥ 11-cell embryos (OR 2.14, 95% CI 1.47-3.11; P < 0.001) than in those transplanted with 8-cell embryos. These results are consistent with those of our study.…”
Section: Discussionmentioning
confidence: 98%
“…Their results showed that for embryos with normal cleavage patterns, developmental potential, implantation, and LBRs increased with cell number. Moreover, Tian et al [15] found that the LBRs were signi cantly higher in patients transplanted with 10-cell embryos (OR 1.62, 95% CI 1.03-2.53; P = 0.035) and ≥ 11-cell embryos (OR 2.14, 95% CI 1.47-3.11; P < 0.001) than in those transplanted with 8-cell embryos. These results are consistent with those of our study.…”
Section: Discussionmentioning
confidence: 98%
“…A low blastomere number in D3 embryos commonly indicates poor prognosis. Studies have con rmed that the transfer of slow-developing embryos results in low implantation rates and LBR [21,22]. In this regard, several possible reasons have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some questions regarding the current consensus on embryo assessment have been raised. Some studies have hypothesized that fast-cleaving embryos have a similar or even higher developmental competence than 8cell embryos [13,21,23,24]. Luna et al [24]demonstrated that fast-cleaving embryos (> 10 cells) not only reach the blastocyst stage at a rate similar to that of intermediate-cleaving embryos (8 cells) but also have a signi cantly greater likelihood of reaching better blastocysts.…”
Section: Discussionmentioning
confidence: 99%
“…Pons MC believed that D3 embryos with more than 11 cell blastomeres had the equivalent developmental potential to those with eight-cell blastomeres (Pons et al, 2019). Tian L used the 8-cell embryo group as a model, and found that patients who received 10-cell and 11-cell embryo transplants had a much higher chance of having a live delivery (Tian et al, 2022). However, some studies have suggested that the pregnancy outcome of fasterdeveloping embryos is lower than that of normal-developing embryos(Martinez-Granados et al, 2018, Racowsky et al, 2011).…”
Section: Discussionmentioning
confidence: 99%